INNOVATIVE SOCIO-CULTURAL PRACTICES DEALING WITH DIFFERENT CATEGORIES OF THE POPULATION: A DIFFERENTIATED APPROACH (Konferensiyalar | Conferences, 2024)
In our increasingly diverse and interconnected world, it is crucial to recognize and value the uniqueness and individual needs of various population categories. Socio-cultural practices that consider these differences are essential for creating inclusive and effective programs and initiatives. This article explores the innovative approaches towards working with different categories of the population, highlighting the importance of a differentiated approach.